Letter from the Michael C. Fina Company - The Michael C. Fina Company:::::: (1976)
A June 30, 1976 letter from Michael C. Fina Co., Inc., a Fifth Avenue jewelry and silverware retailer, invites delegates to the Democratic National Convention to take advantage of special courtesy discounts arranged at the request of the Convention Chairman. The company promotes its reputation as a leading discount jeweler and encourages delegates to visit its store at 580 Fifth Avenue, near Rockefeller Center. The letter emphasizes the exclusive savings available to delegates who present the letter and frames the visit as a memorable New York shopping experience.